Synthesis, electrical and optical properties of 5-indoline-2,3-dione derivatives with Co(II), Ni(II), Cu(II) metal complexes / Muneera Fatin Manan - Manan, Muneera Fatin (2014)
Molecular organic semiconductor has attracted much attention because of its easy to synthesize but it has a weakness in terms of solubility. To overcome, Schiff base ligands and their metal complexes have been selected to test their electrical conductivity values as they are soluble in most organic solvents, facile synthesis and variety of economical starting materials. Yet, until now there are few reports on Schiff base metal complexes that have such properties and the involvement of the effects of substituted group towards the electrical conductivity. In this study, nine Schiff base ligands abbreviated as LI to L9 were synthesize from diketone precursors of isatin, 5- chloroisatin and 5-bromoisatin with different diamine. L1 to L3, L4 to L6 and L5 to L9 were derived from o-phenylenediamine, 4-nitro-o-phenylenediamine, and 4- chloro-o-phenylenediamine respectively. Six metal complexes which are CoL1, NiL1, CuL1, CoL2, CuL2 and CoL3 have been successfully synthesized. All the synthesized compounds were characterized by elemental analysis, NMR spectroscopy, Infrared spectroscopy, molar conductivity and magnetic susceptibility measurement. The Schiff base ligands behave as uninegatively charged bidendate ligands in metal complexes which coordinated to the metal via the azomethine nitrogen and the imino nitrogen atoms. Conductivity studies and the optical properties of these compounds were investigated to determine their conductivity value and energy band gap. The conductivity values obtained were placed between 10¯⁵10¯⁸Ω¯¹cm¯¹which in the range of semiconductor compound and the energy band gap of current OLED material, AIQ₃ (2.70eV) has been selected as a standard value. Based on the result, LI gives the lowest conductivity value (5.3416x10¯⁸Ω¯¹cm¯¹) and highest energy band gap (2.8826eV), while L5 gives highest conductivity value (1.5596x10¯⁶Ω¯¹cm¯¹) and lowest energy band gap (2.1903eV). L4 to L6 series gave high conductivity value and lowest energy band gap because the presence of nitro group. All metal complexes exhibit higher conductivity value and lower energy band gap compared with their respective Schiff base ligand. These findings present a beneficial basis to further apply in electronic industrial application as it will give a better or equivalence quality to improve the current semiconductor problems in terms of solubility and cost. Attempted works on synthesis of metal complexes from remaining Schiff base ligands were also reported.